2008
DOI: 10.1016/j.vaccine.2007.11.091
|View full text |Cite
|
Sign up to set email alerts
|

Willingness of Chinese injection drug users to participate in HIV vaccine trials

Abstract: SummaryBackground-Chinese injection drug users (IDUs) may be a proper candidate population for HIV vaccine trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 24 publications
1
41
1
Order By: Relevance
“…In northwest China (Urumqi City), WTP in HIV preventive vaccine trials among IDUs was 92.0% (74.3% definitely willing and 17.7% most likely willing). WTP was positively associated with a history of sex with a drug-using partner, needle and syringe sharing with a new drug use partner in the past 3 months, perceived family support for participation, and perceived vaccine protection against HIV infection; alternatively, WTP was negatively associated with the perceived risk of social stigma and isolation for participation [19]. In Beijing, WTP of MSM was 70.9% (35.8% definitely willing and 35.1% most likely willing), and the analysis suggested that perceived family support, perceived protection against HIV infection and fear that participation would result in social distancing were associated with WTP [18].…”
Section: Discussionmentioning
confidence: 99%
“…In northwest China (Urumqi City), WTP in HIV preventive vaccine trials among IDUs was 92.0% (74.3% definitely willing and 17.7% most likely willing). WTP was positively associated with a history of sex with a drug-using partner, needle and syringe sharing with a new drug use partner in the past 3 months, perceived family support for participation, and perceived vaccine protection against HIV infection; alternatively, WTP was negatively associated with the perceived risk of social stigma and isolation for participation [19]. In Beijing, WTP of MSM was 70.9% (35.8% definitely willing and 35.1% most likely willing), and the analysis suggested that perceived family support, perceived protection against HIV infection and fear that participation would result in social distancing were associated with WTP [18].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study recently conducted in our area on 326 drug users found WTP in 83% of cases (51% would definitely participate, and 32% would probably participate) (Etcheverry, 2011). In China, a study conducted among 401 IDUs showed a rate of definite WTP of approximately 75%; the rate reached 94% if the group that indicated a probable WTP was included (Yin, 2008). One of the findings among drug users is noteworthy: those who showed an increased risk of infection were the most likely to agree to participate in a phase III vaccine trial.…”
Section: Resultsmentioning
confidence: 95%
“…Research regarding HIV vaccine trials in all populations has also found that those at high risk are more WTP than those with low risk. 2,21 FSWs who had no education or a senior high school education reported that they were more likely to participate in a microbicide trial (75.00%, 60.81%) than FSWs with a primary or junior high school education (51.06%, 46.28%). However, lesseducated FSWs need more help to understand the concepts of a microbicide trial.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 This study found perceived benefits such as protection against HIV infection, free HIV counselling/testing and physical checkups were similar to motivators for participation in HIV vaccine trials. 18,21,25 It is known that enrolling in an HIV prevention intervention trial could cause stigma and discrimination against participants, 26 and FSWs have increased vulnerability to social isolation and economic exploitation. 26,27 In the study sample, physical harm, social discrimination and economic loss were found to be barriers to WTP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation